Educational Resource Development Model from the Perspective of Knowledge-Based View: A Study of State Vocational High Schools in Manado City - Sumual, Herry; Prahani, Binar Kurnia; Soputan, Grace J.; Sumual, Hendro; Sumilat, Juliana Margareta (International Journal of Information Technology and Education, 2025)
In this era of globalization, which is very competitive in various fields of life, vocational education is crucial, considering the increasing demands for human resources in the labor market for middle-class workers. This study aims to determine the implementation of human resource development carried out by schools and to produce a draft of a human resource development model based on the Knowledge-Based View. This study uses a qualitative approach with a case study method. This method is used to obtain needs analysis data in designing a human resource development model in the field of vocational education. The findings of this study indicate that the development of educational resources, more specifically human resources in the education and training elements of the school, has been planned. In addition, it was also found that the development of educational resources, more specifically human resources in the career development element, has several requirements, including work period, credit points, work performance, education and training, and staff development. This study concludes that human resource development in State Vocational High Schools in Manado City has been implemented from planning to implementation.